The unintended consequences of infrastructure development - Antonella Bancalari (The Institute for Fiscal Studies (IFS), 2024)
I investigate the social costs imposed by poor implementation of public infrastructure. Focusing on the period from 2005 to 2015 in Peru, when the government embarked on a nationwide initiative to expand sewerage systems, I leverage quasi-random variation in initiation of the implementation phase. By combining several sources of administrative data, I find that infrastructure development increased infant and under-5 mortality. These effects are driven by health and safety hazards associated with construction work, leading to increased deaths from accidents and waterborne diseases. The severity of these effects is more pronounced in areas where construction activity was more intense.
Keywords: H54; I15; J18; N36; O18; 330; state capacity; public expenditure; public goods; implementation; infrastructure; mortality